Challenges to Healthy Eating Practices: A Qualitative Study of Non-Hispanic Black Men Living With Diabetes. (June 2016) - Lee, Loretta T.; Willig, Amanda L.; Agne, April A.; Locher, Julie L.; Cherrington, Andrea L.
Purpose: The purpose of this study was to explore current dietary practices and perceived barriers to healthy eating in non-Hispanic black men with type 2 diabetes. Methods: Four 90-minute focus groups held in September and October 2011 were led by a trained moderator with a written guide to facilitate discussion on dietary practices and barriers to healthy eating. Participants were recruited from the diabetes database at a public safety-net health system in Jefferson County, Alabama. Two-independent reviewers performed content analysis to identify major themes using a combined deductive and inductive approach. Results: There were 34 male participants aged 18 years and older. Mean years living with diabetes was 9.6 ± 5.9. Sixty-two percent of participants perceived themselves to be in fair or poor health. Participants' self-reported eating practices did not always relate to hunger. Internal cues to eat included habit and response to emotions, and external cues to eat included media messaging, medication regimens, and work schedules. Men identified multiple barriers to healthy eating including hard-to-break habits, limited resources and availability of food at home and in neighborhood grocery stores, and perceived poor communication with health care professionals. Conclusion: Non-Hispanic black men acknowledged the importance of healthy eating as part of diabetes self-management but reported various internal and external challenges that present barriers to healthy eating. Tailored strategies to overcome barriers to healthy eating among non-Hispanic black men should be developed and tested for their impact on diabetes self-management.